EVALUATION OF IMMUNE RESPONSE IN PATIENTS WITH CHRONICLYMPHOCYTIC LEUKEMIA. II: HUMORAL IMMUNE RESPONSE - Al-Dabagh, Muhammed; Al-Mayah, Kasim (Iraqi Journal of Science, 2024)
Chronic lymphocytic leukemia (CLL) is a hematologic malignancy characterized byprogressive accumulation of lymphocytes. This study aimed to evaluate humoralimmunity in patients with CLL via estimation of serum levels of immunoglobulins IgG,IgA, and IgM and two cytokines: interleukin-4 (IL-4) and interleukin-10 (IL-10). Bloodsamples were collected from 48 patients with CLL (28 treated and 20 untreated). Other20 blood samples were collected from healthy individuals as control group. Single radialimmune-diffusion assay was used to estimate the serum levels of immunoglobulins.Enzyme linked immunosorbent assay (ELISA) was used to estimate serum concentrationof IL-4 and IL-10. The study showed unsignificant increase in serum concentration IgGand IL-10 while there was unsignificant decrease in IgA, IgM, and IL-4 in treated anduntreated groups as compared with the healthy control group. These data indicates alittle or unimportant effects of IL-4 and IL-10 on immunoglobulin production in studiedpatients.